Three-Dimensional Stability Characteristics of Finite Electrified Conducting Fluids Streaming through a Porous Medium - T. M. N. Metwaly; Zakaria M. Gharsseldien (Journal of Mathematics)
A novel procedure is utilized to investigate the surface waves between two finite conducting fluids streaming through a porous medium in the presence of a horizontal electric field. Normal mode analysis is applied to study two- and three-dimension disturbances cases. The quadratic dispersion equation of complex coefficients representing the system is derived and discussed. It is noted that based on appropriate data selections, the stability criteria do not depend on the medium permeability. It is found that electrical conductivities, viscosities, medium porosity, and surface tension enhance the stability of the system while the dimension and the fluid velocities decrease the stability of the system. Finally, the fluid depths have a dual role (stabilizing as well as destabilizing effects) on the system.